Analisa Fundamental Dan Analisa Teknikal Pada Rencana Investasi Pasar Modal - Rimawati, Elistya (Jurnal Ilmiah SINUS, 2013)
Stock selection based on high return objectives and risk as low. In stock valuation analysis, investors can perform fundamental analysis of top-down manner to assess the company's prospects. Analysis performed on macroeconomic factors, industry analysis, company analysis, technical analysis. First need to analyze the macroeconomic factors that affect the performance of the entire company, followed by analysis of the industry, and an analysis of the company that issued the securities concerned. Technical analysis can determine the patterns of movement of stock prices in the future based on the observation of the movement of stock prices in the past. Key : Stock selection, analyze macroeconomic, technical analysis